Customer Retention Strategies and Performance of Commercial Banks in Rwanda: A Case Study of Equity Bank Rwanda Public Limited Company (PLC) - Justine , Uwamaria; Njenga, Gitahi (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
The main objective of research was to examine the influence of consumer retention strategies on the performance of Commercial Banks in Rwanda; taking Equity Bank Rwanda PLC as the case study. More specifically the study sought to; examine how consumer retention strategies affect the performance of Equity Bank Rwanda PLC; to determine the performance level of Equity Bank Rwanda PLC; and to establish the relationship between consumer retention strategies and the performance of Equity Bank Rwanda PLC. The study adopted three theories; relationship commitment model, customer bonding theory and disconfirmation of customer satisfaction. The study used descriptive case study research design. The study’s target population was 134 staff members. Slovin’s formula was used to calculate the sample size n=100. Purposive technique of sampling was used dependent on the analyst's judgment that the selected sample matched the study’s objectives. The researcher collected primary data from the respondents using survey questionnaires. Secondary data was sourced from open access libraries and peer reviewed journals relevant to the study. Questionnaires that were accurately completed were assigned with codes and entered into the SPSS computer software for analysis. Data was presented using frequencies, rates, and means, standard deviations, and exhibited as tables. Person correlations and regression examinations were utilized to decide and clarify the connection between study variables. Respondents strongly agreed that products and services presented by the bank meet the needs of the customers (mean 4.54); agreed that; services given by the bank coordinate the requirements of the customers (mean 4.42); accuracy was assured in all bank transactions (mean 4.24); bank officials made follow-ups to ensure that complaints were handled effectively and consumers were satisfied (mean 4.25); and customer complaints were handled immediately (mean 4.08). Respondents strongly agreed that the bank has memorable advertisements that capture significant data with respect to their products and services (mean 4.59); agreed that the bank offered novel and particular items (mean 4.46); the bank used latest technology that had diversified its ability to offer services to customers (mean 4.17); and the adoption of Mobile banking and the frequency of transactions using Money Transfer technologies ‘EazzyPay” had increased the bank’s profitability (mean 4.13). A regression analysis was conducted to determine the influence of consumer retention strategies on bank performance when the dependent variables were regressed against the independent variables. The findings suggested a 65.3% variance of customer retention rates, 75.5% variance of customer growth, and 53.5% variance of Banking operational costs as accounted for by the model, in this case, consumer perceived pricing, service quality delivery, and product diversification. ANOVA results suggested consumer retention rates (p=.006), customer growth (p = .024), Banking operational costs (.003) indicating that the models were significant in predicting the influence of consumer retention strategies on bank performance given that the p values were <0.05 or < 0.01. Conclusions made by the study suggested that Equity bank had adopted customer retention strategies that contribute towards improving its market share. Service quality consumer retention strategies adopted by the bank had contributed towards increment in the quantity of consumers seeking products and services. Product diversity retention strategies had led to high satisfaction rates among consumers. The study recommended that banks should strengthen consumer analysis in order to ensure that it foresees changing needs for more quality products and services.